Medidas antropométricas para la evaluación de la masa muscular en pacientes con enfermedad renal crónica bajo tratamiento conservador - Pereira, Priscila Moreira de Lima; Cándido, Ana paula Carlos (Nutrición Clínica y Dietética Hospitalaria, 2020)
Introduction: Patients with chronic kidney disease (CKD) have increased protein catabolism, leading to worse quality of life, cardiometabolic complications and increased risk of hospitalizations. Nutritional assessment is important, although it has limitations due to changes in body water and bone mass. The aim of the study was to identify the correlation of anthropometric measurements with muscle mass in patients with CKD. Methods: Epidemiological cross-sectional study. Patients with CKD under conservative treatment from 60 years of age were evaluated. We collected: weight, height, BMI, arm circumference (BC), arm muscle circumference (AMC), calf circumference (CC), adductor pollicis muscle thickness (APMT), muscle mass obtained by bipolar and tetrapolar bioimpedance (LTM). Descriptive analyzes were performed and the measurements were correlated with the LTM by Pearson Correlation. The agreement between the methods were tested by the Kappa test. Results: The sample consisted of 137 individuals, 60.6% male, with a mean age of 72.89 ± 7.66 years. In females, only the dominant hand EMAP correlated with the LTM (r = 0.33), whereas in males, all measurements (BMI, CC, BC, AMC, muscle mass and EMAP) showed a moderate correlation. Evaluating the agreement between the classification according to the LTM index and the anthropometric measurements, poor or light agreement was obtained. Discussion: Anthropometric measurements have the following advantages: low cost, fast, easy evaluation and clinical applicability. Among the evaluated measures, the EMAP stands out, which presented a moderate correlation and slight agreement with the muscle mass. Such measure is promising for assessment of nutritional status. Conclusion: The use of anthropometric measurements to assess muscle mass in elderly patients with chronic kidney disease under conservative treatment should be performed and interpreted with caution and in a complementary manner in the assessment of body composition.